Crossing the 49th Parallel : Migration from Canada to the United States, 1900-1930 - Ramirez, Bruno (Book collections on Project MUSE., 2018)
In the hundred years ending in 1930, an estimated 2.8 million Canadians moved south of the 49th Parallel and settled in the United States. The human and technical resources they brought made Canadian immigrants integral to the growth of New England, the Great Lakes region, and the west coast. Crossing the 49th Parallel is the first book to encompass that entire, continent-wide population shift. It brings Canadian migration to the center of both Canadian and U.S. history.Bruno Ramirez researches the contents of previously unused border records to bring to light the wide variety of local contexts and historical circumstances that led Canadian men, women, and children to cross the border and become key actors in the U.S. economy and society. Ramirez goes beyond these statistical data, consulting qualitative sources and case studies to reveal the motives and aspirations of individuals and family groups.The comparative perspective of Crossing the 49th Parallel allows Ramirez to explain the distinctive roles of French- and Anglo-Canadians in the immigrant movement. By shifting the viewpoint from a continental to a transatlantic one, Ramirez also unveils Canada's important role in international migration; it served as a temporary destination for many Europeans who subsequently remigrated to the United States.